Pengenalan dan Pengendalian Hama dan Penyakit Pada Tanaman Ubi Kayu di Unit Pelaksana Teknis Badan Penyuluhan Pertanian (UPTBPP) Kulim - Hafiz Fauzana; Rusli Rustam; Nelvia Nelvia; Desita Salbiah; Yunel Venita; Irfandri Irfandri (Unri Conference Series: Community Engagement, 2021)
Cassava (Manihot utilissima) is the third food source in Indonesia. Cassava commodity has economic value and is widely planted in the Technical Implementation Unit of the Agricultural Extension Agency (UPTBPP) Kulim, Pekanbaru City. This service aims to provide knowledge and skills to cassava farmers in the Technical Implementation Unit of the Kulim Agricultural Extension Agency (UPTBPP) of Pekanbaru Municipality about the types of pests and diseases that attack, symptoms of attacks, and their control techniques. The target of service is mainly cassava farmers in the Technical Implementation Unit of the Agricultural Extension Agency (UPTBPP) Kulim Pekanbaru Municipality so that farmers' incomes become better and more prosperous. The service method used the method of counseling and demonstration. The extension method uses LCD and infocus, pictures of pests, life cycles, damage are presented, along with explanations of control techniques. The demonstration method includes the practice of control techniques consisting of first introducing natural enemies in the form of videos, making glumon traps and making forest betel leaf and soursop vegetable pesticides. The measuring instrument for achieving the goals of service was the understanding and knowledge of farmers about pests and diseases of cassava plants, controlling cassava pests and changing farmers' views on pest control no longer prioritizing the use of synthetic pesticides and the ability of farmers to recognize the types of natural enemies of pests. Achievement is measured by distributing questionnaires to determine changes and increase in farmer knowledge. The results of the service program in the form of counseling and demonstrations were very well responded by cassava farmers. Participants paid close attention, asked many questions. The results of the questionnaire assessment of farmers showed an increase in farmers' understanding of controlling pests and diseases of cassava plants after service activities. Thus this service will provide great benefits to cassava farmers in controlling pests and diseases in cassava cultivation.